Environment as a cognitive prosthesis : an architecture of interdependence that reimagines the traditional sources of social solidarity for the New Agers in Danville - Barker, A.A.J. (Arthur Adrian Johnson) (University of Pretoria, 2023)
Mini Dissertation (MArch (Prof))--University of Pretoria, 2022.